Pengaruh Celebrity Endorsement dan Citra Merek terhadap Kepercayaan Merek dan Niat Beli Produk Kecantikan - Aditha Amalia Salsabila; Albari Albari (Publikasi Indonesia, 2022)
This study aims to explain the effect of celebrity endorsement and brand image on brand trust and purchase intention of beauty products. Researchers used convenience sampling to collect information from the desired target. Hypothesis testing in this study uses descriptive analysis which is processed with the help of Statistical Product and Service Solutions (SPSS) software as many as 50 respondents to test whether this question is in accordance with its measurement function and the questionnaire can be understood, besides that Structural Equation Modeling (SEM) analysis which is processed with the help of SmartPLS software as many as 150 respondents. The results of this study indicate that the variables Celebrity Endorsement, Brand Image and Brand Trust have a positive and significant effect on Purchase Intention.